Pelatihan Deteksi Jenis-Jenis Pencemaran Udara Sebagai Usaha Peningkatan Keterampilan Identifikasi - Sujarta, Puguh; Suharno, Suharno; Rahayu, Irma; Kabes, Wetty Q.M.A. (JURNAL PENGABDIAN PAPUA, 2025)
The impact of development has risks for society, one of the impacts of development is the emergence or occurrence of environmental pollution. The objectives of the service activities: (1) introduce a training program to detection of air pollution; (2) through service it can produce output in the form of a national service journal. This activity was held on August 9, 2024 at SMKS YPKP TIK Sentani Jayapura. The target audience involved in this activity are high school students. The selection of the target audience is based on the tasks and obligations of students to build Adiwiyata High School that loves the environment. The methods used in the implementation of this activity are lectures, simulations and practice on how to harvest and use it. The conclusion is that: (1) Participants are very enthusiastic about participating in service activities and understand air pollution, its types, impacts and detections; (2) based on the evaluation results, it shows that the level of understanding of the participants is quite good when seen from the percentage of all participants' opinions.